(2x-3)+1=17

Simple and best practice solution for (2x-3)+1=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)+1=17 equation:


Simplifying
(2x + -3) + 1 = 17

Reorder the terms:
(-3 + 2x) + 1 = 17

Remove parenthesis around (-3 + 2x)
-3 + 2x + 1 = 17

Reorder the terms:
-3 + 1 + 2x = 17

Combine like terms: -3 + 1 = -2
-2 + 2x = 17

Solving
-2 + 2x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 2x = 17 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 17 + 2
2x = 17 + 2

Combine like terms: 17 + 2 = 19
2x = 19

Divide each side by '2'.
x = 9.5

Simplifying
x = 9.5

See similar equations:

| 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 | | 21x-28= | | h=-16t^2+16t+112 | | -3(x-1)+8(x-3)=6x-5x | | -5k-7=-37 | | p/2=3/4+p/3 | | x=9x^3-6x^2 | | y=10+-7(0) | | -k-3k-2k=-36 | | -z-4z=-65 | | 3/2x+1/5=3/4 | | y=10-7(-2) | | (0.1x-21)=180 | | 2a^5-8a^4-24a^3= | | 8.2-r=5r | | 15=35x | | -3x(2x+4)=0 | | (48+2x)(72+2x)-3456=0 | | 3a=9b-12 | | (0.1x+29)=180 |

Equations solver categories